2019
DOI: 10.3390/agriengineering1020014
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Potency of Activated Carbon Powder Derived from Cultivated Marine Microalgae as a Promising Filler in Mixed Matrix Membranes

Abstract: Activated carbon-filled mixed matrix membranes were commonly used to enhance the separation performance of liquid or gas separation processes. Activated carbon is traditionally derived from agricultural crops such as coconut shells or wood biomass. Marine microalgae however have a great potential to produce powdered activated carbon. In this study, marine microalgae Chlorella vulgaris have been evaluated for their carbon content, and the 16.09% carbon content has potential to be employed as a raw material in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The increase of ash content of the activated carbon was caused by the oxidation reaction during the physical activation, which reduced the adsorption capabilities. This is mainly due to pores clogged by various minerals including Ca and K. The deposition of minerals on the surface of activated carbon was also reported by Sukoyo et al (2019). As noted by Husillos Rodríguez et al (2016), the largest components found in activated carbon ash were Si, Fe, and S. The EDXRF result reveals that distilled water post treatment decreased the ash forming elements including Fe, K, and Ca.…”
Section: Elemental Analysis Of Raw Materials and Distilled Water Post-treated Activated Carbonsupporting
confidence: 60%
“…The increase of ash content of the activated carbon was caused by the oxidation reaction during the physical activation, which reduced the adsorption capabilities. This is mainly due to pores clogged by various minerals including Ca and K. The deposition of minerals on the surface of activated carbon was also reported by Sukoyo et al (2019). As noted by Husillos Rodríguez et al (2016), the largest components found in activated carbon ash were Si, Fe, and S. The EDXRF result reveals that distilled water post treatment decreased the ash forming elements including Fe, K, and Ca.…”
Section: Elemental Analysis Of Raw Materials and Distilled Water Post-treated Activated Carbonsupporting
confidence: 60%
“…and its absorption of iodine was used for the synthesis of nano-activated carbon 19) . This synthesis was carried out by chemical activation assisted by ultrasonic waves with a frequency of 28 KHz for 45 minutes, then allowed to stand for 24 hours at room temperature and filtered.…”
Section: Synthesis Of Nano-activated Carbonmentioning
confidence: 99%
“…Commercial activated carbon commonly derived from bituminous coal, coconut shell, and woods [13]. Recent studies reported the manufacture of activated carbon from other biomass source, such as oil palm empty fruit bunch [14,15], palm shell [16], langsat (Lansium domesticum) empty fruit bunch waste [17], coconut leaves [18], pine cone shell [19] and microalgae [20]. Most of the studies reveals the potency of agricultural biowaste as activated carbon sources.…”
Section: Introductionmentioning
confidence: 99%